Pengaruh Budaya Organisasi dan Komitmen Organisasi terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening pada Dinas Pemuda dan Olahraga Kebudayaan dan Pariwisata Kabupaten Labuhanbatu - Indri Liza Karina; Junita Lubis; Pitriyani Pitriyani (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
This study was conducted at the Youth and Sports Culture and Tourism Office of Labuhanbatu Regency with the aim of analyzing the influence of organizational culture and organizational commitment on the performance produced by employees with job satisfaction as an intervening variable. This study uses a quantitative method with the help of the IBM SPSS 25 Software analysis tool. This research was tested using path analysis, t-test, and determination coefficient test. The results of the study show that: 1) organizational culture (X1) has a positive and significant influence on job satisfaction (Z); 2) organizational commitment (X2) has a positive and significant influence on job satisfaction (Z); 3) job satisfaction (Z) has a positive and significant influence on employee performance.